El trasvase instalado en la laguna Choclococha vulnera un bien jurídico tutelado de la persona al acceso del agua, anexo de Huaracco - Huancavelica - Auris Bellido, David Silvio (2023)
The purpose of this research was to elucidate the violation of water access in the annex of Huaracco, caused by the Choclococha diversion. The study focused on the dynamics between the State and society concerning water resource management. The aim was to grant participation to various users within a management unit, considering this unit as the entire watershed. The redistribution of the resource was proposed through a water market and/or a center for the exchange of usage rights, allowing specific or definitive changes to the originally granted use, with the goal of promoting good governance. The management of this proposal rested with a River Basin Organization as a regulatory body, endowed with legal capacity for sustainable management and protection of water utilization within its flow, considering the different uses and users throughout the entire watershed. It was crucial for the high Pampas watershed to be considered untouchable for community members in influence areas lacking water resources to satisfy their needs. The redistribution of the resource was envisaged through a needs assessment, carried out through educational outreach and socialization in the sectors involved in the communities.